VOLKANISME DAN KEPUNAHAN MANUSIA PURBA DI KOMPLEK GUNUNG PATIAYAM, DESA JEKULO, KECAMATAN KUDUS, JAWA TENGAH - Mulyaningsih, S.; Bronto, S.; Kusnaedi, A.; Simon, I.; Prasetyanto, I. W. (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Geomorphologically, Mount Patiayam is a dome. The dome is characterized by varrying in strike-dips, the dipping layers of the southern part is to south, the eastern part is to east, the northern part is to north and the western part is to west. The summit of the dome is composed of igneous rock of pyroxenic basalt, while fluvial deposits and shale are composing of flanks up to foot of the dome. Based on the composing rocks, there were volcanism processes within Mount Patiayam. The interpretation was also supported by Landsat image that showed depression-shapes in caldera rings-like.Furthermore, Pleistocene sediments contain vertebrate and hominid (Homo erectus) fossils that are exposed at Patiayam region. Those fossils occur within cross bedding structure of pumiceous breccia, fine up to very coarse tuffs, and clay tuffs.